An Economic Projection to 2050: The OECD "ENV-Linkages" Model Baseline - Château, Jean (OECD Environment Working Papers, 2011)
This document describes economic baseline projections to 2050 for several world regions. It describes how socio-economic drivers are used to create a consistent projection of economic activity for the coming decades, applying the general framework of "conditional convergence". This economic baseline is created using the ENV-Linkages model version 3. This baseline is used for modelling analysis with the ENVLinkages model as carried out for the OECD Environmental Outlook to 2050 (to be released in Spring 2012). Specific attention is given in this paper to projections for the energy system as part of the economy, to allow detailed links between economic activity and environmental pressures, including emissions of greenhouse gases (GHGs)